Evaluation of Burn Wound Infection in a Referral Center in Colombia - Jaimes, Sandra L.; Ramírez, Carlos E.; Viviescas, Andres F.; Abril, Andres F.; Flórez, David F.; Sosa, Cristian D. (Indian Journal of Plastic Surgery, 2022)
Introduction Burn wound infection (BWI) is the second most important cause of death in burn patients. There is currently limited data about the incidence and clinical presentation of BWI using quantitative techniques as quantitative biopsy culture (QBC) to prevent progress to burn wound sepsis (BWS).Methods This is a prospective cohort study of patients diagnosed with BWI, confirmed by QBC, from February 2018 to July 2019 at University Hospital of Santander (HUS). The primary outcome was to determine clinical, microbiological, and histopathological characteristics of patients diagnosed with BWI along with a positive QBC and their relationship with early diagnosis and progression to BWS.Results 525 patients were admitted to HUS Burn Center. Of those, 44/525 (8.23%) presented a clinical diagnosis of BWI (median age, 20.5 years [1–67 years]; 25/44 [56.8%] male). QBC was positive in 26/44 (59%), Staphylococcus aureus 14/44 (31.8%), and Pseudomonas aeruginosa 7/44 (15.9%) were the mainly etiological agents isolated. Bacterial resistance to antibiotics was mostly to beta-lactams in 14/44 (31.8%), corresponding to methicillin-resistant Staphylococcus aureus (MRSA). Clinical signs more related to infection were erythema in 33/44 (61.3%). As many as 10/44 (22.7%) progressed to sepsis and 2/44 (6%) died.Conclusion BWI increases hospitalization time and number of surgeries, increasing the risk of sepsis and death. The QBC allows an accurate diagnosis with lesser false-positive cases that impact antibiotic resistance and mortality. Protocols targeting this problem are needed to decrease the impact of this.
Keywords: Burn Wound; Burn Wound Infection; Burn Wound Sepsis; Quantitative Biopsy Culture